Effects of high-intensity interval training on executive functions and IGF-1 levels in sedentary young women: a randomized controlled trial - Jimenez-Roldán, Manuel Jesús; Sañudo Corrales, Borja; Carrasco Páez, Luis (Frontiers in Sports and Active Living, 2025)
PurposeSedentary behavior and physical inactivity are widespread among university students, negatively impacting physical and neurocognitive health. Executive functions and insulin-like growth factor 1 (IGF-1) are adversely affected by inactivity. Moreover, physical activity increases IGF-1 concentrations, which may mediate beneficial effects on brain health and cognitive performance. The effect of HIIT exercise combined with increased physical activity on these variables is not well understood. This study evaluated the chronic effects of HIIT, with or without increased physical activity, over 12 weeks of training and a 12-week follow-up period, on executive functions and IGF-1 concentrations in sedentary young university students.MethodThis randomized controlled trial included 77 sedentary female university students, assigned to three groups: HIIT (n = 25), HIIT plus increased daily physical activity (HIIT + PA, n = 25), and control group (CG, n = 27). The intervention involved assessments at baseline (T1), post-intervention (T2), and after a 12-week follow-up (T3). Salivary IGF-1 concentrations were measured using enzyme-linked immunosorbent assay (ELISA). Executive functions were evaluated with the Stroop Test, Wisconsin Card Sorting Test, and Digit Span Test. The HIIT protocol consisted of 40-min sessions, three times per week, delivered online. The HIIT + PA group also aimed to complete 10,000 steps per day.ResultsNo statistically significant changes in IGF-1 concentrations were found over time or between groups, although descriptive increases were observed in both HIIT and HIIT + PA groups at follow-up. For executive functions, improvements over time were found in cognitive flexibility (WCST) and working memory (DST-B and DST-T), but without significant group × time interactions. Only WCST-E-P showed a significant group effect (p = 0.028), indicating possible differences between groups in cognitive rigidity. The HIIT + PA group showed a tendency toward improved inhibitory control (Stroop accuracy), although this was not supported by significant interaction effects. Working memory improvements (DST-B) were significant over time, especially in the HIIT group, but again without significant differences between groups.ConclusionA 12-week HIIT program, with or without increased daily physical activity, can lead to improvements in executive functions in sedentary young women, particularly in working memory and cognitive flexibility. However, these changes were not exclusive to the intervention groups, suggesting possible contributions from repeated testing or other external factors. While IGF-1 levels showed upward trends, no significant group-level effects were confirmed. These findings highlight the potential cognitive benefits of HIIT but emphasize the need for further research with tighter controls and objective neurobiological measures to clarify the mechanisms involved. Incorporating HIIT into student routines may support cognitive health, but broader lifestyle interventions may be needed to sustain long-term benefits.